The Book of Acts : form, style, and theology - Dibelius, Martin, 1883-1947.; Hanson, K. C. (Kenneth C.) (Minneapolis : Fortress Press, 2004)
"The legacy of Dibelius lives on in numerous ways. His form-critical work was foundational for Gospel studies, which moved on after the war to redaction criticism. His focus on literary aspects of the book of Acts was a precursor to much of the work in New Testament literary criticism today. And questions of setting in life (Sitz im Leben) were important for laying the foundation of current emphases in social history and social-scientific criticism. But like other great scholars (such as Wellhausen, Gunkel, and Bultmann), his work is not only of interest for historical reasons - his insights and groundbreaking analyses remain standards for contemporary research. And while the exegesis of the book of Acts continues, it does so on the shoulders of Dibelius and the work presented in the essays included here."--BOOK JACKET.
1. Acts in the setting of the history of early Christian literature -- 2. The first Christian historian -- 3. The book of Acts as an historical source -- 4. Style criticism of the book of Acts -- 5. The speeches in Acts and ancient historiography -- 6. Paul in the book of Acts -- 7. Paul on the Areopagus -- 8. Paul in Athens -- 9. The Apostolic Council -- 10. The conversion of Cornelius -- 11. The text of Acts.
Includes bibliographical references (p. 204-214) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc